Status of gender parity in the Ethiopian general education - Aster Minwyelet; Meskerem Cheru (Bahir Dar Journal of Education)
The main purpose of this study is to critically examine as to how the education sector is moving towards gender parity in primary and secondary education in terms of school enrollment related issues, male-female teacher ratio, gender sensitiveness of facilities, and study barriers for achieving gender parity. Document review was used to collect data from official documents including the six years' educational statistics annual abstracts, the recent Education for All global monitoring report, the Education Sector Development Programs and different research reports. The documents were mainly examined by focusing on the four areas (parameters) listed above. The result indicated that there is a remarkable improvement in gender parity across the years in both primary and secondary schools in terms of female students’ enrolment. However, there are problems in dropout, repetition, and completion rates and different barriers are affecting girls' education that negatively influences the move towards achieving gender parity especially in secondary schools. Implications of the outcomes of the study for practice and research are described.